Verifica-UD: a Verifier for Universal Dependencies Annotation for Portuguese - Lopes, Lucelene; Duran, Magali Sanches; Pardo, Thiago Alexandre Salgueiro (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL), 2023)
This paper presents Verifica-UD, a web-based tool to detect problems in Portuguese sentences annotated using Universal Dependencies (UD) standards in the form of a CoNLL-U file. The tool performs three levels of sentence verification: structural (to assess CoNLL-U compliance), morphosyntactic (to assess the part of speech tagging), and syntactic (to assess the parsing information). Verifica-UD also provides detailed help on Portuguese UD annotation directives. The benefits of this tool for reviewing annotated corpora are illustrated with an experiment.